The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/0300-1652.108900
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, ulcer grade and management outcome of diabetic foot ulcers in a Tropical Tertiary Care Hospital

Abstract: Background:The objective was to determine the risk factors, ulcer grade, and management outcome of patients with diabetic foot ulcers (DFU) managed in a tropical tertiary hospital.Materials and Methods:This is a prospective observational study of all consecutive diabetes mellitus (DM) patients with DFU admitted in the University of Benin Teaching Hospital, Benin City, Nigeria over a 26-month period. Data documented included age, gender, type of DM, duration of DM, risk factors of DFU, duration of DFU, Wagner's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 14 publications
8
30
1
Order By: Relevance
“…Similarly, patients who had wound infection at presentation were less likely to have had foot care education {(OR-0.444 (95% CI = 0.258-0.764) p = 0.003} and those who suffered death were less likely to have had foot care education {(OR-0.779 (95% CI = 0.410-1.480). Similar things applied to those who engaged in barefoot walking {(OR-0.512 (95% CI has been reported in similar studies around the world, where the most productive age groups are often the worst hit [16][17][18]. Our study also revealed that the males were more often the ones affected, probably because they are more active in out-door activities such as farming, mining and other high risk manual labours, as they are most of the time the breadwinners of their family.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Similarly, patients who had wound infection at presentation were less likely to have had foot care education {(OR-0.444 (95% CI = 0.258-0.764) p = 0.003} and those who suffered death were less likely to have had foot care education {(OR-0.779 (95% CI = 0.410-1.480). Similar things applied to those who engaged in barefoot walking {(OR-0.512 (95% CI has been reported in similar studies around the world, where the most productive age groups are often the worst hit [16][17][18]. Our study also revealed that the males were more often the ones affected, probably because they are more active in out-door activities such as farming, mining and other high risk manual labours, as they are most of the time the breadwinners of their family.…”
Section: Discussionsupporting
confidence: 59%
“…Footcare education has long been advocated as an essential strategy of prevention of DFU, and has been widely practiced in the developed world [13][14][15]. The same cannot be said of our centres in Nigeria and the rest of the developing world, especially in Sub-Saharan Africa, where certified foot care educators and podiatrists are a rarity even in our referral centres [16][17][18]. The health system is often poorly organised, ill-equipped with poor referral system that provide incomplete coverage for the total diabetes population, majority of whom are at the understaffed primary healthcare level [18].…”
Section: Methodsmentioning
confidence: 99%
“…Statistically, there was low insignificant correlation between these two variables as given in table (6) and figure (3). ulcers classification were the most common prevalence 30% in ulcers of diabetic patients, and these results were compatible with other studies conducted in different countries [13][14][15], but disagree with a previous study reported that Wagner's grade 2 and 3 ulcers were the most common prevalence [16]. Grade 4 was the lowest prevalence in this study, and this contrast with other studies revealed that the grade 4 was the most common prevalence in DFU [17,18].…”
Section: Bacterial Species Of Dfu Associated With Wagner's Grades Systemcontrasting
confidence: 54%
“…Early diagnosis and presentation to hospital for prompt treatment of DFU is capable of reducing the significant morbidity and mortality associated with this condition. [2] Early detection of peripheral neuropathy and patient's education regarding foot care and footwear is crucial in reducing risk of any injury that can lead to ulcer formation. This study has been undertaken to identify risk factors and assess the level of awareness of diabetic foot care among diabetic population reporting to our hospital.…”
Section: Introductionmentioning
confidence: 99%